Contemporary Issues in International Business and Entrepreneurship. - Torkkeli, Lasse (Cambridge Scholars Publisher, 2021)
This book illustrates the impact of increasingly prominent global phenomena, such as digitalisation and climate change, on the international activities of both small and large multinationals. As it highlights, extant management research does not fully explain such emergent topics as Internet platforms, digital business models, and the decision-making of cleantech and circular economy companies. This volume serves to fill this lacuna.